Optimization and comparative evaluation of optical and photocatalytic properties of TiO2 thin films prepared via sol–gel method - Mohd. Danish; Subia Ambreen; Arti Chauhan; Ashutosh Pandey (Journal of Saudi Chemical Society)
TiO2 thin films were fabricated with optimization of the synthesis parameters for efficient photocatalysis. The films were sculptured from gels obtained from Ti(OiPr)4 and Ti(OBus)4 via spin coating at different rotation speed ranging from 1000 rpm to 3000 rpm. Thicknesses of the films were in the range of ≈112–160 nm. The X-ray diffractograms showed a phase transformation from anatase to rutile along with an increase in average crystallite size from 11 nm to 18 nm with a decrease in thickness of the films. Refractive index (n) values of the films were in the range of 2.50–3.45 while extinction coefficient (k) values ranged from 0.090 to 0.860. These films were transparent with high transmittance (T ⩽ 95%) in the visible region. The optical band gaps for films were calculated to be in the range of 3.00–3.95 eV. Photocatalytic degradations of methylene blue by the fabricated TiO2 thin films have also been investigated.